2015
DOI: 10.5847/wjem.j.1920-8642.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the Australasian Triage Scale: a meta-analysis

Abstract: BACKGROUND: Although the Australasian Triage Scale (ATS) has been developed two decades ago, its reliability has not been defi ned; therefore, we present a meta-analyis of the reliability of the ATS in order to reveal to what extent the ATS is reliable.DATA SOURCES: Electronic databases were searched to March 2014. The included studies were those that reported samples size, reliability coefficients, and adequate description of the ATS reliability assessment. The guidelines for reporting reliability and agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 25 publications
0
47
0
2
Order By: Relevance
“…Data collection includes referral source (self-referred, general practice, specialist, nursing home), mode of arrival (self-referral, ambulance), hospital facility, triage category (Australasian triage category),6 7 presenting problem, mode of separation (admitted to hospital, discharged or died). Presenting problems allocated by triage nurses at the point of patient arrival to ED were categorised into broad clinical groups by the investigating team (see table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Data collection includes referral source (self-referred, general practice, specialist, nursing home), mode of arrival (self-referral, ambulance), hospital facility, triage category (Australasian triage category),6 7 presenting problem, mode of separation (admitted to hospital, discharged or died). Presenting problems allocated by triage nurses at the point of patient arrival to ED were categorised into broad clinical groups by the investigating team (see table 1).…”
Section: Methodsmentioning
confidence: 99%
“…[7,8] The organization of out-of-hour services in primary care has changed, with new models such as large GP cooperatives (GPCs) and primary care centres integrated into EDs. [9][10][11] In the Netherlands, the proportion of self-referrals at EDs is approximately 30%. [12] Almost all Dutch citizens have a GP and basic health insurance.…”
Section: Introductionmentioning
confidence: 99%
“…5 7 9 10 In addition, two meta-analyses including studies of 'live' triage and the triage of paper case scenarios reported correlation coefficients of 0.60 and 0.77 for the CTAS and ESI, respectively, whereas a meta-analysis including only studies applying the triage of paper case scenarios reported a correlation coefficient of 0.40 for the ATS. [13][14][15] One factor that may contribute to errors in triage is that triage decisions are based to a large extent on informed but subjective estimates of the patient's presenting condition, such as estimates of pain and future resource utilisation in the ATS and ESI, respectively. 16 17 Another negative factor may be the complexities of triage systems with large numbers of different presenting complaints.…”
Section: Introductionmentioning
confidence: 99%